I. .

  1. I.
  2. II.
  3. II.
  4. . . .
  5. 8.

1: .

1. , :

) 1) 2) 3) 4)

5) 6) 7) 8)

9) 10) 11) 12)

13) 14) 15) 16)

17) 18) 19) 20)

21) 22) 23) 24)

25) 26) 27) 28)

1) 2) 3) 4)

5) 6) 7) 8)

9) 10) 11) 12)

13) 14) 15) 16)

17) 18) 19) 20) 21) 22) 23)

24) 25)

1) 2) 3) 4)

5) 6) 7)

8) 9) 10) 11)

12) 13) 14) 15)

16)

D) 1) _ 2) 3) 4) 5)

6) 7) 8) 9) 10)

E) 1) 2) 3) 4) 5)

6) 7) 8) 9) 10)

11) 12) 13) 14) 15) 16) 17) 18) 19) 20)

II. :

.1.a) b) c)

2. a) b) c)

3. a) b) c)

4. a) b) c)

5. a) b) c)

6. a) b) c)

7. a) b) c)

8. a) b) c)

9. a) b) c)

10. a) b) c)

.1) 2) 3) 4)

5) 6) 7) 8) 9)

10) 11) 12) 13)

14) 15) 16)

17) 18) 19) 20) 21) 22) 23) 24) 25)

26) 27) 28)

29) 30) 31) 32)

33) 34) 35)

.1) 2) 3) 4)

5) 6) 7) 8)

9) 10) 11) 12) 13)

D. :

1)x = t-sint, y = 2-cost; 2)x = e-t, Y = arcsint; 3)x = sint + cost, y = sin2t;

4)x = tg2t, y = cos2t; 5)x = sint, y = ln (cost); 6)x = etsint, y = t + sint

7) 8) 9) 10)

11)

E. /

1)x + cos (xy) = 5; 2)2xy-3y2x + x = 9; 3)x-2ycosy2= 0; 4)xex-y-sinx + 10 = 0;

; ylnx + xlny = 7; 5xy + cosx + siny = 0

5) tgy = 4y-5x 6)y = 7x-ctgx 7)yx-6 = cosx 8)y = ey+ 4x 9)4sin2(X + y) = x

10) y2+ x2= siny 11) y2= X + cosy 12)lny-y / x = 7 13)xy2-y3= 4x-5 14)x + arctgy = y

F. ,

1) 2) 3) 4) 5)

6) 7) 8) 9)

G. ,

1) 2) 3) 4) 5) 6) 7)y= ln(1-x2)

8) 9) 10) 11) 12)

H. -,

1) 2) 3) 4) 5)

6) 7) 8) 9) 10)

.

1) 2) 3) 4) 5) y = 6) 7) y = xe-x

8) 9) 10) 11) 12)

13) 14) 15)

L.

y = 16x2(X-1)2y = x2(X-2)2y = 2x3+ 3x2-5 Y = (x-1)2(X-3)2y = - (x-2)2(X-6)2/ 16

y = x (12-x2) / 8 y = - (x2-4)2/ 16 y = (2x-1)2(2x-3)2



28. | 2:
© um.co.ua -